Cyberloafing at the workplace: age and gender differences - Ahmad, Aminah; Omar, Zoharah (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Cyberloafing is a form of deviant workplace behavior which involves the use of organizations’ internet access by employees during working hours for non-work purposes. Recently, there is an increasing interest among researchers on cyberloafing at the workplace among employees due to the negative consequences of this behavior. This paper presents a literature review of age and gender differences in cyberloafing by describing the pattern of involvement among younger and older employees as well as male and female employees. Implications for organizations in formulating prevention–intervention policies on internet abuse at the workplace is also presented.